2007
DOI: 10.1002/art.22424
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma asymmetric dimethyl‐L‐arginine levels are linked to endothelial progenitor cell depletion and carotid atherosclerosis in rheumatoid arthritis

Abstract: Plasma asymmetric dimethyl-L-arginine levels are elevated in RA patients free of cardiovascular disease or risk factors. Asymmetric dimethyl-L-arginine accumulation may contribute to endothelial progenitor cell depletion via depressed NO-dependent endothelial progenitor cell mobilization and/or survival, with consequent impairment of endothelial progenitor cell-mediated endothelial repair, which can promote atherogenesis in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 64 publications
4
65
0
2
Order By: Relevance
“…Our results support both Turiel et al [22,30] and Surdacki et al studies [21,31] in terms of the relation between ADMA and inflammation. Surdacki et al displayed that neither ADMA nor SDMA (symmetric dimethylarginine) were correlated with the disease activity and inflammatory activation [21,31]. It has also been shown [30] that anti-inflammatuar therapy had no effect on ADMA levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results support both Turiel et al [22,30] and Surdacki et al studies [21,31] in terms of the relation between ADMA and inflammation. Surdacki et al displayed that neither ADMA nor SDMA (symmetric dimethylarginine) were correlated with the disease activity and inflammatory activation [21,31]. It has also been shown [30] that anti-inflammatuar therapy had no effect on ADMA levels.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the authors suggested that increased ADMA levels were related with the decrease in CFR [3]. Although one study [21] showed an association between ADMA and common carotid intimae media thickness (IMT), other studies failed to find a relation between ADMA levels and IMT [22,23]. A decrease in DDAH activity may be one of the reasons of high ADMA levels in the RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Surdacki et al (30), it was reported that ADMA levels and carotid IMT values were higher in patients with RA compared to the control group and that ADMA levels and carotid IMT values were correlated. Kiani et al (31) found high ADMA levels in patients with systemic lupus erythematosus (SLE) and an association between these levels and coronary calcium level.…”
Section: Discussionmentioning
confidence: 96%
“…In the general population, carotid ultrasound has been used for cardiovascular risk stratification; Intimal-Medial Thickness (IMT) and plaque are associated with clinical CVD and have independent prognostic value for such CV events [14]. In 2 studies of Asian patients [15,16] and in a study from Poland [17], carotid IMT was increased in patients with RA compared with matched controls. In addition, patients with RA had a similar carotid IMT and prevalence of carotid plaque as with age-and gender-matched patients with type 2 diabetes mellitus.…”
Section: Subclinical Atherosclerosis Carotid Intima-media Thicknessmentioning
confidence: 99%